A Standalone PV System with a Hybrid P&O MPPT Optimization Technique - Hota, S.; Sahu, M. K.; Malla, J. M. R. (Engineering, Technology & Applied Science Research, 2017)
In this paper a maximum power point tracking (MPPT) design for a photovoltaic (PV) system using a hybrid optimization technique is proposed. For maximum power transfer, maximum harvestable power from a PV cell in a dynamically changing surrounding should be known. The proposed technique is compared with the conventional Perturb and Observe (P&O) technique. A comparative analysis of power-voltage and current-voltage characteristics of a PV cell with and without the MPPT module when connected to the grid was performed in SIMULINK, to demonstrate the increment in the efficiency of the PV module after using the MPPT module.